The response of a high voltage transformer with various geometries of core joint design - Alyozbaky, Omar Sh.; Mohd Isa, Maryam; Ab Kadir, Mohd Zainal Abidin; Izadi, Mahdi (Universiti Putra Malaysia Press, 2017)
The core losses in a three phase transformer can be significantly reduced by improving the core joint geometry. The researchers were applied numerous types of T-joint designs in order to reach the optimum design that can be used in three phase transformer to reduction the losses. Two types of T-joint design are presented in this paper; T-joint with 90° butt-lap design and T-joint with 45° mitered design. A 3-phase distribution transformer was simulated in 3D using Ansys Maxwell software. The core loss for a three-leg three phase transformer rated 1000 KVA and the flux density distribution are investigated. The simulation results show the core losses were increased up to 3% and the flux density was increased to reach more than 22% flux density become higher when using T-joint with 90° butt-lap design as compared with T-joint with 45° mitered design.